Estratégias alternativas de imuno-modulação nas doenças inflamatórias intestinais - Ana Cristina Gomes Santos (2011)
To maintain intestinal homeostasis, the immune system must faithfully respond to antigens from pathogenic microbes while maintaining a state of tolerance to commensal microorganisms and food antigens that confront it every day. However, disruption of this thin balance can cause inflammatory bowel disease (IBD) in genetic susceptible hosts. IL-10 is a regulatory cytokine that plays a major role in the homeostasis of the gut mucosa and this is illustrated by the fact that IL-10-deficient mice develop spontaneous colitis. In this study, IL-10-/- mice were analyzed for immunological changes accompanying the development of colitis at different ages. Defects in regulatory elements at the gut mucosa such as lower frequency of CD4+CD25+Foxp3+ T cells could be detected since 6 weeks of age. In parallel, there was an increased frequency of activated T cells in the colon. Colitis progression culminates with the reduction in the frequency of TCRγδ+ intraepithelial lymphocytes (IEL) and CD4+LAP+ regulatory T cells in the small and large intestines. Production of IL-17 was higher in the colon at 6 weeks of age but at 16 weeks of age levels of IFN-increased in the colon. TGF-β was increased in the proximal jejunum of mice with colitis. Frequencies of B1 cells were elevated in peritoneum, Peyer´s patches and gut lamina propria. There were alterations in serum immunoglobulin levels and secretory IgA production was increased. Despite all these alterations, 16-week-old IL-10-deficient mice could be rendered tolerant by a continuous feeding protocol of antigen administration. We next tested two therapeutic alternatives for the treatment of IBD. The first one consisted of a diet where proteins were replaced by free aminoacids or short chain peptides. The diet containing free aminoacids aggravated gut inflammation in DSS induced colitis model with reduction in secretory IgA. Likewise, the diet with protein hydrolizates was not able to ameliorate the acute colitis. As a second therapeutic alternative, we used a strain of Lactococcus lactis genetically engineered to deliver Hsp65 in the gut mucosa. Oral administration of Hsp65-producing L. lactis prevented DSSinduced colitis; abolishing weight loss, diarrhea and fecal bleeding. The effectcould not be explained by alterations in secretory IgA or in intestinal permeability. However, mucosal protection was accompanied by diminished levels of TNF-, IL-6, IL-4 and IL-5 and by enhanced IL-10 in colonic mucosa. In addition, mice treated with Hsp65-producing L. lactis had increased frequency Treg cells in the spleen. Moreover, the ratio between effector T cells and Tregs was similar to the one found in control health mice. There was enhanced frequency of dendritic cells expressing CD80, CD86, CD40, CD103, TLR2 e TLR4 in the spleen of mice that received Hsp65-producing L. lactis. Ability of Hsp supernatant in enhancing expression of TLR2 and TLR4 was confirmad in vitro. Moreover, Hsp65-producing L. lactis did not improve the ulcerative colitis in TLR2-/-. In IL-10-/- mice, Hsp65-producing L. lactis was able to reduce the signs of inflammation. Likewise, frequency of CD4+LAP+ Tregs and colonic levels of TGF- increased after treatment with Hsp65-producing L. lactis. Our study provides detailed analysis of changes that precede colitis in genetically susceptible mice and it also suggests that Hsp-65 producing L. lactis could be one alternative treatment to IBD.